Skulptur i Parken. - Trädgardsföreningen, Göteborg (Göteborg : Stad Göteborg, 1986)
Anderson, Roland ; Berggren, Eva ; Bozajic, Rino ; Ignell, Britt C ; Eduards, Gudrun ; Hake, Claes ; Hansson, Lars ; Hybbinette, Pieter ; Jern, Britt-Marie ; Johansson, Henry ; Lagergren, Anne ; Lengstrand, Bertil ; Leyman, Fred ; Lindekrantz, Lars ; Lindfeldt, Berit ; etc.
Skulptur i Parken, Trädgardsföreningen, Göteborg, 16 maj - 31 augusti 1986
boek